HUBUNGAN MENTORING DENGAN KEBERHASILAN MAHASISWA EKONOMI SYARIAH PADA MATA KULIAH AKUNTANSI - FARIDAH, ROHANA; MUBARAK, ZAKI (At-Taradhi, 2014)
The purpose of this research is to find out how affective a mentoring program that was held by Islamic Economics Departement, Sharia and Islamic Economics Faculty and to find out the relationship between result of mentoring program and accounting subject. The methodology that isused in this research is quantitative with Wicoxon Test and Spearman Correlation Analysis. This study shows that mentoring program in accounting subject which was given to the student at second semester doing effectively. Spearman Correlation Analysis shows that the student get a great point in both mentoring program and accounting subject.